Private Berlin : Private #5 - Patterson, James, 1947-; Sullivan, Mark T.; Fliakos, Ari; LaVoy, January (New York : Hachette Audio, 2013)
The Berlin office of the world's most renowned investigation firm looks into the disappearance of an agent, Chris Schneider, whose last case involved an unfaithful billionaire, a cheating soccer player, and a seedy nightclub owner.
Unabridged.
Compact discs.
Read by Ari Fliakos and January LaVoy.
Keywords: Missing persons -- Fiction; Private security services -- Fiction; Private investigators -- Fiction; Suspense fiction; Audiobooks